2023
DOI: 10.1021/acs.est.2c08644
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 6-PPD Quinone at Environmentally Relevant Concentrations Causes Abnormal Locomotion Behaviors and Neurodegeneration in Caenorhabditis elegans

Abstract: 6-PPD quinone (6-PPDQ) can be transformed from 6-PPD through ozonation. Nevertheless, the potential neurotoxicity of 6-PPDQ after long-term exposure and the underlying mechanism are largely unclear. In Caenorhabditis elegans, we here observed that 0.1–10 μg/L of 6-PPDQ caused several forms of abnormal locomotion behaviors. Meanwhile, the neurodegeneration of D-type motor neurons was observed in 10 μg/L of 6-PPDQ-exposed nematodes. The observed neurodegeneration was associated with the activation of the Ca2+ ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…The exposure concentrations of 6-PPDQ were 0.1, 1, and 10 μg/L, which were selected as described. , Currently, concentrations of 6-PPDQ in runoff water, river, wastewater, and drinking water vary from ng/L to μg/L . The highest concentration of 6-PPDQ was reported in roadway runoff (19 μg/L) .…”
Section: Methodsmentioning
confidence: 99%
“…The exposure concentrations of 6-PPDQ were 0.1, 1, and 10 μg/L, which were selected as described. , Currently, concentrations of 6-PPDQ in runoff water, river, wastewater, and drinking water vary from ng/L to μg/L . The highest concentration of 6-PPDQ was reported in roadway runoff (19 μg/L) .…”
Section: Methodsmentioning
confidence: 99%
“…These results raise concerns about the potential health effects of 6PPD and 6PPDQ, especially during pregnancy. Studies have suggested that 6PPD and 6PPDQ can cause developmental and neurotoxicity in vitro and in zebrafish and elegan models. For example, 6PPDQ can form DNA adducts in mammalian cells, indicating potential for teratogenic effects . Exposure to 6PPDQ caused abnormal locomotion behaviors in Caenorhabditis elegans at 0.1–10 μg/L and neurodegeneration at 10 μg/L .…”
Section: Introductionmentioning
confidence: 99%
“…26 Exposure to 6PPDQ caused abnormal locomotion behaviors in Caenorhabditis elegans at 0.1−10 μg/L and neurodegeneration at 10 μg/L. 27 postfertilization) caused morphological changes, behavioral toxicity, and cardiotoxicity in zebrafish larvae. 28 Exposure of zebrafish embryos to 6PPD (0.22 mg/L; 2−120 h postfertilization) caused developmental toxicity and altered hormone levels and gene expressions in embryos.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6-PPD reacts with ground-level ozone to produce 6-PPDQ and other oxidized byproducts . Since the discovery of 6-PPDQ, acute toxicity at environmentally relevant (ng to μg/L) concentrations has been established for several species including white-spotted char (Salvelinus leucomaenis), rainbow trout (Oncorhynchus mykiss), brook trout (Salvelinus fontinalus), and early-life stage Chinook (Oncorhynchus tshawytscha). Further, several groups have identified sublethal effects of 6-PPDQ (intestinal, neural) , across multiple species including Caenorhabditis elegans, mice, and fathead minnow (Pimephales promelas) . While the mechanism of 6-PPDQ toxicity is still being uncovered, Mahoney et al recently reported in vitro evidence that 6-PPDQ toxicity may be mediated by disruption of mitochondrial respiration and Blair et al have observed disruption of the blood–brain barrier in coho salmon treated with roadway runoff …”
Section: Introductionmentioning
confidence: 99%